Perceptions, impacts, and rewards of row planting - Vandercasteelen, Joachim; Regassa, Mekdim Dereje; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
The Ethiopian government rolled out a nationwide campaign in 2013 to promote the use of row planting, aiming to scale up its adoption to almost 2.5 million teff farmers. However, the impacts of the widespread promotion campaign of row planting of teff in particular on land and labor productivity are unknown. This is mainly due to a lack of reliable and objective farm-level data. Moreover, no systematic effort has yet been put into examining farmers’ perceptions after they experimented with the new sowing techniques. The contribution of this The contribution of this chapter is to analyze the impact of the promotion campaign of row planting of teff and to infer farmers’ perception about the new planting technique and the promotion thereof. To do so, data were collected during the “pre-scale-up” phase of the promotion campaign in 2012/2013 by surveying farmers from 40 villages exposed to the promotion campaign. Data was collected by means of a large-scale randomized control trial (RCT), randomly assigning teff farmers to implement either row planting or broadcasting of teff seed on an experimental plot. The effect of receiving a promotion campaign for sowing teff seeds in rows, together with a reduced seed rate (this combination is referred to as row planting), was measured on teff farmers’ land, as well as on labor productivity.